Analisis Efisiensi Saluran Pemasaran Cabai Rawit di Berbagai Pola Distribusi: Sebuah Tinjauan Literatur - Mustajib Mustajib; Della Ananda Hariningtyas; Delia Syaski Putri; Rahaesal Fathan Asbi; Purana Indrawan (Jurnal Manajemen dan Budaya, 2026)
Bird's eye chili (Capsicum frutescens L.) is a strategic horticultural commodity in Indonesia that frequently experiences price fluctuations due to its perishable nature and inefficient supply chains. This study aims to identify dominant distribution channel patterns, analyze comparative marketing efficiency using marketing margin and farmer’s share approaches, and examine the factors causing inefficiencies across various production centers in Indonesia. The study employs a literature review method, analyzing 24 accredited national and international journal articles published between 2020 and 2025. Data synthesis indicates that the two-tier channel (Farmer → Collector → Retailer → Consumer) is the most dominant distribution pattern across regions due to its effectiveness in product aggregation. Efficiency analysis reveals a negative correlation between distribution channel length and farmer’s share, and a positive correlation with marketing margins. The most efficient marketing channels were found in direct distribution models (zero-tier) and institutional innovations—such as the Auction Market in Sleman—which were able to reduce margins to IDR 5,000/kg.